2012
DOI: 10.3389/fnhum.2011.00183
|View full text |Cite
|
Sign up to set email alerts
|

Influence of meditation on anti-correlated networks in the brain

Abstract: Human experiences can be broadly divided into those that are external and related to interaction with the environment, and experiences that are internal and self-related. The cerebral cortex appears to be divided into two corresponding systems: an “extrinsic” system composed of brain areas that respond more to external stimuli and tasks and an “intrinsic” system composed of brain areas that respond less to external stimuli and tasks. These two broad brain systems seem to compete with each other, such that thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(150 citation statements)
references
References 61 publications
(102 reference statements)
4
140
0
6
Order By: Relevance
“…In one there is greater attention to external stimuli in the environment, and in the other attention is focused on internal and selfrelated stimuli including self-projection into the past, such as during remembering, and selfprojection into the future, such as during future planning (Josipovic, Dinstein, Weber and Heeger 2011). These two modes of experience appear to correspond to two competing cortical brain systems; the extrinsic system that responds most to external stimuli and tasks, and the intrinsic system that responds most to internal stimuli and tasks (e.g., Golland et al 2007;Tian et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one there is greater attention to external stimuli in the environment, and in the other attention is focused on internal and selfrelated stimuli including self-projection into the past, such as during remembering, and selfprojection into the future, such as during future planning (Josipovic, Dinstein, Weber and Heeger 2011). These two modes of experience appear to correspond to two competing cortical brain systems; the extrinsic system that responds most to external stimuli and tasks, and the intrinsic system that responds most to internal stimuli and tasks (e.g., Golland et al 2007;Tian et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Josipovic et al (2011) showed that focused attention meditation increases the anti-correlation between the extrinsic and intrinsic brain systems. It thus appears that momentary self-awareness, which increases following mindfulness training, emphasises the extrinsic mode of experiencing whereas narrative self-awareness (the default mode of processing) emphasises the intrinsic mode of experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the possible neural mechanisms of such large-scale integration, recent research (Josipovic et al, 2012) shows that nondual awareness meditation results in an increase of functional connectivity, and by inference in the underlying synchronization, between large-scale globally distributed neural networks Á the intrinsic default mode network and the extrinsic task-positive network. As hypothesized elsewhere (Josipovic, in press), a network for nondual awareness may provide an organizing center, re-contextualizing the activity of other networks and attractors involved in representing experience during a ''nondual state.''…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Josipovic et al (2011) have reported a restructuring of the usual anti-correlation between brain regions involved in external, task-oriented processing versus those involved in internal, self-related processing. This restructuring took place specifically during a type of mindfulness meditation that Josipovic et al refer to as non-dual awareness (NDA).…”
Section: Religion Brain and Behavior 53mentioning
confidence: 99%
“…A combination of these and other methods are often practiced in a single sitting. Meta-analysis of the neurocorrelates of meditation have shown that across these diverse practices and varied years of experience, the most common effect appears to be modulation of a network of brain regions called the default mode network (DMN) (Tomasino et al, 2012(Tomasino et al, , 2014Fox et al 2014;Simon and Engström 2015;Josipovic 2014;Josipovic et al 2012). The DMN is a constellation of brain regions silently active when we are passive, which has provided a new view into the elusive nature of meditative practice.…”
Section: Introductionmentioning
confidence: 99%